Hyaluronic Acid Based Hydrogels for Regenerative Medicine Applications. (19th May 2015) - Borzacchiello, Assunta; Russo, Luisa; Malle, Birgitte M.; Schwach-Abdellaoui, Khadija; Ambrosio, Luigi
Abstract : Hyaluronic acid (HA) hydrogels, obtained by cross-linking HA molecules with divinyl sulfone (DVS) based on a simple, reproducible, and safe process that does not employ any organic solvents, were developed. Owing to an innovative preparation method the resulting homogeneous hydrogels do not contain any detectable residual cross-linking agent and are easier to inject through a fine needle. HA hydrogels were characterized in terms of degradation and biological properties, viscoelasticity, injectability, and network structural parameters. They exhibit a rheological behaviour typical of strong gels and show improved viscoelastic properties by increasing HA concentration and decreasing HA/DVS weight ratio. Furthermore, it was demonstrated that processes such as sterilization and extrusion through clinical needles do not imply significant alteration of viscoelastic properties. Both SANS and rheological tests indicated that the cross-links appear to compact the network, resulting in a reduction of the mesh size by increasing the cross-linker amount. In vitro degradation tests of the HA hydrogels demonstrated that these new hydrogels show a good stability against enzymatic degradation, which increases by increasing HA concentration and decreasing HA/DVS weight ratio. Finally, the hydrogels show a good biocompatibility confirmed by in vitro tests.